I-Musafir with Al-Fatihah colour coded tajweed learning: a mobile application / Geogiana Buja … [et al.] - Buja, Geogiana; Mohd Taher, Muhammad Saiful Islami; Abu Bakar, Ahmad Yumni; Zainal Abidin, Nurul Aini; Kamarazaman, Moramisha (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Human ingenuity in the creation and innovation emerged over the years driven by biological and social factors. Everything is for people to live a life. Nowadays, the world is filled with all sorts of technology creation. One of that is mobile technology which really gives impact on improvement of people's life. Besides, mobile technology also satisfies people's needs in many different ways. In terms of religion, there is several applications available in the Internet. Therefore, this project will propose a mobile application that can support the needs of the Muslim to perform their Jamak prayer with l-Musafir and also learning the Al-Fatihah with enhanced colour coded Tajweed. The audio-visual element is included in the application for engaging people in the learning process. This will create a more interactive learning environment